Effects of Oils and Essential Oils from Seeds of Zanthoxylum schinifolium against Foodborne Viral Surrogates. (18th December 2014) - Oh, Mi; Chung, Mi Sook
Abstract : Human noroviruses are the most frequent cause of foodborne viral disease and are responsible for the vast majority of nonbacterial gastroenteritis. However, no specific therapies are available for the efficient control or prevention of foodborne viral disease. Here, we determined the antiviral activities of oils from seeds of Zanthoxylum schinifolium (ZSO) against foodborne viral surrogates, feline calicivirus-F9 (FCV-F9), and murine norovirus-1 (MNV-1), using plaque assay. Time-of-addition experiments were designed to determine the antiviral mechanism of action of ZSO against the surrogates. Maximal antiviral effect was observed upon pretreatment of FCV-F9 or MNV-1 with ZSO, which comprised oleic acid, linoleic acid, palmitic acid, and linolenic acid as the major fatty acids. FCV-F9 was more sensitive to ZSO than MNV-1, and the 50% effective concentration of ZSO against pretreatment of FCV-F9 was 0.0007%. However, essential oils from Z. schinifolium (ZSE), which comprised 42% estragole, showed no inhibitory effects against FCV-F9 and MNV-1. These results suggest that the inhibitory activities of ZSO were exerted by direct interaction of FCV-F9 or MNV-1 virion with ZSO, which may be a food material candidate for control of foodborne viral disease.